Water vapor electrolysis hydrogen production battery

By using a polymer containing alkaline groups as a phosphoric acid carrier, it enhances its binding with phosphoric acid, and solves the problem of insufficient stability of dielectric electrolytic water vapor hydrogen production technology under high voltage and high relative humidity conditions, and achieves a stable electrolytic water vapor hydrogen production effect under dielectric temperature conditions.

CN120174393APending Publication Date: 2025-06-20DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311738948.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-18
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

The existing dielectric electrolytic water vapor hydrogen production technology is insufficient in stability under high voltage and high relative humidity conditions, and the rapid precipitation of phosphoric acid leads to unstable system performance.

Method used

A polymer containing alkaline groups is used as a phosphoric acid support to enhance the binding of the polymer support and phosphoric acid through ion pair interaction, improve the proton transfer ability of the catalyst layer, and ensure proton transfer in the membrane and the catalyst layer under dielectric temperature conditions.

Benefits of technology

The stable operation of electrolyzed water vapor to produce hydrogen under dielectric temperature conditions (100 to 250 degrees Celsius), improves the stability and performance of the system, and avoids the problem of rapid precipitation of phosphoric acid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120174393A_ABST
    Figure CN120174393A_ABST
Patent Text Reader

Abstract

The invention discloses a water vapor electrolysis hydrogen production battery. The water vapor electrolysis hydrogen production battery comprises an exchange membrane, a cathode and anode catalyst layer, a cathode and anode diffusion layer and water vapor, a cathode and anode catalyst layer is arranged on the outer side of the exchange membrane, and a cathode and anode diffusion layer is arranged on the outer side of the cathode and anode catalyst layer; the exchange membrane is a high-molecular polymer containing a basic group; the cathode and anode catalyst layer comprises a high-molecular polymer containing a basic group and a cathode and anode catalyst; and the cathode and anode diffusion layer is selected from one or more of carbon paper, titanium felt and titanium mesh. According to the invention, a high-molecular polymer containing a basic group is used as a phosphoric acid carrier, and the combination of the high-molecular carrier and phosphoric acid is enhanced through the ion pair interaction between the basic group and phosphoric acid, so that the polymer ion exchange capacity (IEC) in a catalyst layer is improved, and the proton transfer rate in the membrane and the catalyst layer is accelerated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a hydrogen production cell by electrolysis of water vapor, belonging to the technical field of hydrogen production by electrolysis of water. Background Art

[0002] Currently, common water electrolysis hydrogen production technologies are mainly divided into two categories: low temperature and high temperature. Among them, low-temperature electrolysis of liquid water usually refers to alkaline water electrolysis and proton exchange membrane electrolysis of water. Its technology is mature and commercialized, and its reaction temperature generally does not exceed 90 degrees Celsius. The high-temperature electrolysis of water vapor hydrogen production device represented by proton conductive ceramics and solid oxides as electrolytes needs to operate at a high temperature of 550 or even 700 degrees Celsius. The advantage is that the high temperature of the system accelerates the reaction kinetics of the electrode. However, the high temperature also limits the stability of the electrode and solid electrolyte materials, and the water vapor also needs to be preheated before entering the system. At present, high-temperature electrolysis of water vapor has not yet achieved large-scale commercial operation.

[0003] There is a huge temperature range between low-temperature and high-temperature water electrolysis, which is called dielectric temperature. Media such as heteropolyacids, tetravalent metal pyrophosphates, and solid acids can transfer protons under dielectric temperature conditions, and molten alkalis (such as lithium hydroxide, sodium hydroxide, potassium hydroxide, etc.) can also conduct hydroxide (approximately 150 to 600 degrees Celsius). However, although the above-mentioned electrolytes have certain proton or hydroxide conductivity under dielectric temperature conditions, the performance and stability of the overall system for electrolyzing water vapor are still very poor, and are still in the laboratory exploration stage. Common Nafion membranes require liquid water to help their sulfonic acid groups complete proton transfer, and under dielectric temperature conditions above 100 degrees Celsius, the vaporization of liquid water causes the proton conductivity of Nafion itself to decrease rapidly. Nafion composite membranes doped with oxide particles such as silicon oxide can increase its water retention capacity above 100 degrees Celsius, thereby improving its proton conduction efficiency, and can increase its operating temperature to 120 degrees Celsius or even higher, but it still cannot cover the medium temperature conditions of 100-250 degrees Celsius. At the same time, the stability of the composite membrane is far less than that of the Nafion membrane under low temperature conditions. In addition, the use of polybenzimidazole (PBI) doped with small molecule phosphoric acid can also achieve proton transfer in the range of 120-200 degrees Celsius. It is mainly used in medium temperature proton exchange membrane fuel cells, operating in the absence of water and low relative humidity. However, the reaction conditions of proton exchange membrane electrolysis of water vapor are harsh, and the potential difference between the positive and negative electrodes can be as high as 1.8V or more. At the same time, water vapor, as a necessary reactant, will greatly increase the relative humidity of the system, thereby exacerbating the loss of phosphoric acid.

[0004] For electrolytes such as solid acids, heteropolyacids, and molten alkalis that operate under medium-temperature conditions, the ionic conductivities reported in the current literature within the range of 100 - 250 °C are generally low, resulting in an increase in the internal resistance of the system, a low current density, and insufficient stability. Some of the above electrolytes reach a relatively high ionic conductivity at higher temperatures (above 300 °C).

[0005] Nafion doped with water-retaining substances can also raise the temperature of proton exchange membrane electrolysis of water at low temperatures to around 130 °C (liquid water under pressure or gaseous water vapor), and the highest operating temperature reported in the literature can reach 180 °C with still a certain proton conduction efficiency. Generally speaking, its proton conductivity decreases rapidly with the increase in temperature, so most can only operate below 150 °C and the stability is also lacking. Summary of the Invention

[0006] Aiming at the above problems existing in the current field of medium-temperature electrolysis of water vapor, especially the problem that after PBI is doped with phosphoric acid, it cannot adapt to the conditions of high voltage and high relative humidity, and the rapid precipitation of phosphoric acid leads to insufficient system stability. In this application, a polymer containing basic groups is used as the carrier of phosphoric acid. According to the requirements of the water vapor electrolysis hydrogen production battery system, the ion exchange membrane and ionomer are respectively regulated, thereby preparing a membrane electrode and assembling a single cell, realizing the electrolysis of water vapor to produce hydrogen under medium-temperature conditions (100 to 250 °C).

[0007] The present invention uses a polymer with an ion pair interaction as the carrier of phosphoric acid, with a quaternary ammonium group as the positive charge center. Through the ion pair interaction, the binding between the polymer carrier and phosphoric acid is strengthened, the ion exchange capacity (IEC) of the polymer in the catalyst layer is improved, and the proton transfer in the membrane and the catalyst layer is ensured under conditions of relatively high relative humidity (RH).

[0008] According to one aspect of the present application, a water vapor electrolysis hydrogen production battery is provided, and the water vapor electrolysis hydrogen production battery includes an exchange membrane, anode and cathode catalyst layers, anode and cathode diffusion layers, and water vapor;

[0009] The anode and cathode catalyst layers are provided on the outer sides of the exchange membrane, and the anode and cathode diffusion layers are provided on the outer sides of the anode and cathode catalyst layers;

[0010] The anion exchange membrane is selected from at least one of polymers I containing quaternary ammonium salt groups;

[0011] The anode and cathode catalyst layers include the catalysts and ionomers of the anode and cathode;

[0012] The ionomer is selected from at least one of polymers II containing quaternary ammonium salt groups;

[0013] The anode and cathode diffusion layers are selected from at least one of carbon paper, titanium felt, and titanium mesh.

[0014] Optionally, the operating temperature of the electrolytic water vapor hydrogen production cell is medium temperature.

[0015] Optionally, the medium temperature is 100 - 250 °C.

[0016] Optionally, the medium temperature is independently selected from any value among 100 °C, 120 °C, 140 °C, 150 °C, 160 °C, 180 °C, 200 °C, 220 °C, 250 °C or the range values between any two of the above.

[0017] Optionally, the polymer I containing a quaternary ammonium salt group and the polymer II containing a quaternary ammonium salt group are independently selected from at least one of polymers containing a trimethylammonium group, polymers containing a piperidine group, and polymers containing an imidazole group.

[0018] Optionally, in the ion exchange membrane, the ion exchange capacity of the quaternary ammonium group, that is, the degree of quaternization is 70 - 100%.

[0019] Optionally, in the anode and cathode catalyst layers, the dosage of the polymer II containing a quaternary ammonium salt group is 20 - 80 wt%.

[0020] Optionally, in the anode and cathode catalyst layers, the dosage of the polymer II containing a quaternary ammonium salt group is 30 - 50 wt%.

[0021] Optionally, the water vapor enters the electrolytic water vapor hydrogen production cell from the anode end through water.

[0022] Optionally, the water injection rate is 0.02 - 1.0 mL / min.

[0023] Optionally, the water injection rate is independently selected from 0.02 mL / cm 2 min, 0.05 mL / cm 2 min, 0.1 mL / cm 2 min, 0.2 mL / min, 0.3 mL / cm 2 min, 0.4 mL / cm 2 min, 0.5 mL / cm 2 min, 0.6 mL / cm 2 min, 0.7 mL / cm 2 min, 0.8 mL / cm 2 min, 0.9 mL / cm 2 min, 1.0 mL / cm 2 min or the range values between any two of the above.

[0024] As an optional implementation, the present application is realized through the following technical solutions:

[0025] Synthesis of quaternary ammonium group polymers. Common quaternary ammonium groups include trimethylammonium (TMA), piperidinium, imidazolium, etc. Here, piperidine is taken as an example for illustration. The synthesis method is based on the literature (Nature Energy 2019, 4, 392 - 398). Piperidinone, p - terphenyl, and trifluoroacetophenone are used to synthesize polytriphenylpiperidine, and then iodomethane is used for quaternization. Among them, the ion exchange capacity of the polymer can be regulated by the ratio of trifluoroacetophenone to piperidinone. The specific synthesis route is as follows:

[0026]

[0027] An ion - exchange membrane is prepared from the piperidine polymer synthesized using the above - mentioned synthesis route, and an ionomer solution is prepared by dispersion. Then, the ionomer solution is dispersed with the cathode (Pt / C) and the anode catalyst (IrO2) in a liquid to prepare a catalyst slurry. The catalyst slurry is then coated on the gas diffusion layer of each respective electrode to prepare a gas diffusion electrode (GDE). Then, the above - mentioned anion - exchange membrane and gas diffusion electrode are soaked in phosphoric acid.

[0028] In the present invention, an anion - exchange membrane and an ionomer containing a quaternary ammonium group synthesized using the above - mentioned synthesis route are used to replace the existing polybenzimidazole membrane as the carrier for phosphoric acid, enhancing the interaction between the carrier and phosphoric acid, and inhibiting the precipitation of phosphoric acid from the membrane electrode under the conditions of medium - temperature water vapor and high voltage. Different ion - exchange capacities are used in the membrane and the ionomer respectively. On the premise of ensuring the mechanical properties of the membrane, the concentration of phosphoric acid in the membrane is increased. For the catalyst layer, the polymer ionomer not only ensures the proton transfer between it and the membrane, but also ensures the contact between the catalyst layer and the gas diffusion layer to prevent the shedding of the catalyst layer.

[0029] Finally, a membrane electrode is formed using a gas diffusion electrode doped with phosphoric acid and the membrane. Then, it is assembled into an electrolytic cell using gaskets and a single - cell test fixture, and tested using an electrochemical workstation, including polarization curves, high - frequency impedance, constant - current tests, etc. During the test, nitrogen is used as the carrier gas at the anode to introduce heated water vapor, and the temperature of the electrolytic cell is between 100 and 250 degrees Celsius.

[0030] The beneficial effects that the present application can produce include:

[0031] 1) The hydrogen - producing electrolytic cell provided by the present application fills the gap in the system operating temperature between solid oxides, proton ceramics for high - temperature electrolysis of water vapor, and traditional low - temperature electrolysis of water. The electrolytic water - vapor - producing hydrogen cell system can electrolyze water vapor under medium - temperature conditions (100 to 250 degrees Celsius).

[0032] 2) The hydrogen production battery by electrolyzing water vapor provided by this application uses ion-pair interaction as the basis, and a polymer with a quaternary ammonium group as the positive charge center is used as the carrier of phosphoric acid. Through ion-pair interaction, the binding between the polymer carrier and phosphoric acid is strengthened, the ion exchange capacity (IEC) of the polymer in the catalyst layer is improved, and proton transfer in the membrane and the catalyst layer is ensured under conditions of relatively high relative humidity (RH). Description of the Drawings

[0033] Figure 1 It is the representative nuclear magnetic hydrogen spectrum of the piperidine terphenyl polymer synthesized in Example 1 of this application.

[0034] Figure 2 In the examples of this application, (a) is the system performance diagram of using a PBI membrane doped with phosphoric acid, and (b) is the system performance diagram of using a quaternary ammonium cation and phosphoric acid under the condition of the same water inflow. Detailed Description of the Invention

[0035] The following describes this application in detail with reference to the examples, but this application is not limited to these examples.

[0036] Unless otherwise specified, the raw materials in the examples of this application are all purchased through commercial channels.

[0037] This application uses a liquid nuclear magnetic resonance spectrometer with the model of Bruker AVANCE III HD 400MHz from Germany; an electrochemical workstation with the model of Bio-Logic SP-50e / 150e from France for characterization.

[0038] Example 1

[0039] Step 1: Synthesis of an anion exchange membrane containing a piperidine group: Dissolve 80 mmol of piperidone, 10 mmol of trifluoroacetophenone, and 90 mmol of p-terphenyl in 80 mL of dichloromethane. Under the reaction condition of stirring in an ice bath at 0 °C, add 75 mL of trifluoromethanesulfonic acid and 6 mL of trifluoroacetic acid, and synthesize polytriphenylpiperidine by superacid catalysis. Then use 10 mL of methyl iodide for quaternization. After quaternization, replace the iodide ions with 300 g of sodium chloride and 300 g of bicarbonate in sequence to synthesize a piperidine polymer membrane with a high IEC. By adjusting the ratio of piperidone to trifluoroacetophenone, the ion exchange capacity of the polymer is controlled. As Figure 1 shown, it is the nuclear magnetic hydrogen spectrum of the synthesized piperidine terphenyl polymer before and after quaternization, and the solvent is deuterated dimethyl sulfoxide. The results show that all the nitrogen-methyl peaks disappear and are all converted into the methyl peaks on the quaternary ammonium salt, and the quaternization degree is 100%.

[0040] Step 2: Synthesis of the anion exchange ionomer containing a piperidine group, which is similar to the synthesis process of the above-mentioned anion exchange membrane containing a piperidine group. The difference is that 60 mmol of piperidone and 30 mmol of trifluoroacetophenone are added to the raw materials to reduce the proportion of piperidone, so as to realize the regulation of the ion exchange capacity of the ionomer. After the ion exchange is completed, it is dispersed with ethanol to obtain an ionomer solution with a mass concentration of 5%.

[0041] Step 3: In the fume hood, 10 mg of Pt / C (TKK TEC10V50E) (cathode) and 10 mg of IrO2 (Sinero) (anode) catalysts are each mixed with 0.2 mL of the ionomer solution, 0.5 mL of deionized water, and 0.5 mL of isopropanol obtained in Step 2, and then ultrasonically treated for 30 minutes to obtain the catalyst dispersions of the cathode and anode. Then, the cathode dispersion is evenly coated on two 2 cm x 2 cm carbon papers, and the anode catalyst dispersion is evenly coated on two 2 cm x 2 cm platinum-plated titanium felts, and dried in air at a temperature of 50 °C to obtain the electrodes of the cathode and anode catalysts.

[0042] Step 4: The cathode and anode catalyst electrodes obtained in Step 3 and the ion exchange membrane prepared in Step 1 are first immersed in 1 M KOH solution for 3 hours, then washed with deionized water, and air-dried at room temperature; then immersed in 85% phosphoric acid solution for 6 hours to obtain the cathode and anode electrodes.

[0043] Step 5: Assemble the cathode and anode electrodes, membrane, gasket, and test fixture obtained in Step 4 into an electrolytic cell. First, dry nitrogen is introduced into both poles of the electrolytic cell, and then heated so that the temperature is controlled to be stable between 100 and 250 °C for about 30 minutes. Then, water vapor is introduced into the anodic end of the electrolytic cell. The water vapor enters the water vapor generation device from deionized water through a plunger pump, and the carrier gas is nitrogen. Among them, the injection rate of deionized water is controlled between 0.02 mL / cm 2 min and 1.0 mL / cm 2 min.

[0044] Step 6: Use an electrochemical workstation to test its polarization curve (scan rate of 20 mV / s) in the voltage range of 1.2 V to 2.0 V, and complete the activation of the membrane electrode; then conduct the electrolytic water vapor stability test at a current density of 100 mA / cm 2 to 300 mA / cm 2 .

[0045] Example 2

[0046] Replace the membranes and ionomers with piperidine functional groups in the first and second steps of Example 1 with alkyltrimethylammonium (TMA) cation functional groups. That is, react polychlorostyrene with trimethylamine and 4-fluorophenethylamine in a dimethyl sulfoxide solution, and then use 1M KOH to exchange the anions to hydroxide to obtain a matrix for fixing phosphoric acid. The other steps are the same as those in Example 1.

[0047] Example 3

[0048] The anion exchange membrane is still the membrane with piperidine functional groups, and the anion exchange ionomer is replaced with the alkyltrimethylammonium (TMA) cation functional groups in Example 2. The other steps are the same as those in Example 1.

[0049] Example 4

[0050] The anion exchange membrane is the membrane with alkyltrimethylammonium (TMA) cation functional groups in Example 2, and the anion exchange ionomer still has piperidine functional groups.

[0051] Comparative Example 1

[0052] As Figure 2 shown, Figure 2 (a) and Figure 2 (b) show the system performance of using a PBI membrane doped with phosphoric acid. As the amount of water vapor entering the system increases (shown as the flow rate of liquid water in the figure, which is heated and vaporized and then enters the electrolytic cell), the initial performance of the system improves, but the voltage rises rapidly. At a constant current density of 100 mA / cm 2 and a water inlet flow rate of 0.50 mL / min, the system voltage rises by more than 100 mV within two hours. Figure (b) shows that using a quaternary ammonium cation to form an electron pair with phosphoric acid under the same condition of a water inlet flow rate of 0.50 mL / min can significantly improve the system stability, and it can operate stably for more than 30 hours at a constant current density of 100 mA / cm 2 .

[0053] Figure 2 (a) and Figure 2 (b) show that using PBI as the base membrane, the stability of its system is significantly lower than that of the system using a terphenylpiperidine membrane. The membrane using PBI doped with phosphoric acid can also conduct protons in the temperature range of 120 to 200 degrees Celsius and is mostly used in intermediate-temperature fuel cells. The system is basically in a state of anhydrous or very low water vapor content. Under the condition of intermediate-temperature electrolysis of water vapor, the loss of phosphoric acid is relatively fast, and the voltage rises relatively fast, rising by more than 100 mV within two hours, as Figure 2 (a) shows.

[0054] Comparative Example 2

[0055] The ion exchange membrane is still a membrane with piperidine functional groups, and the ionomer is replaced by a PBI polymer. The stability of the battery is reduced, and under the conditions of high water vapor flow (>0.5 mL / cm 2 min) and high current density (>200 mA / cm 2 ), the accelerated precipitation of phosphoric acid occurs, resulting in a rapid decline in performance.

[0056] Comparative Example 3

[0057] The ion exchange membrane is a PBI membrane, and the ionomer is a membrane with piperidine functional groups. The battery performance is similar to that of Comparative Example 2, that is, the stability is reduced.

[0058] As described above, these are only several embodiments of the present application, and do not impose any form of limitation on the present application. Although the present application is disclosed with preferred embodiments as above, it is not intended to limit the present application. Any person skilled in the art, without departing from the technical solution of the present application, making some changes or modifications using the technical content disclosed above is equivalent to equivalent implementation cases and all fall within the scope of the technical solution.

Claims

1. An electrolytic water vapor hydrogen production battery, characterized in that, The electrolytic water vapor hydrogen production cell includes an exchange membrane, cathode and anode catalyst layers, cathode and anode diffusion layers, and water vapor; The cathode and anode catalyst layers are provided on the outer sides of the exchange membrane, and the cathode and anode diffusion layers are provided on the outer sides of the cathode and anode catalyst layers; The anion exchange membrane is selected from at least one of polymers I containing quaternary ammonium salt groups; The cathode and anode catalyst layers include the catalysts and ionomers of the cathode and anode; The ionomer is selected from at least one of polymers II containing quaternary ammonium salt groups; The cathode and anode diffusion layers are selected from at least one of carbon paper, titanium felt, and titanium mesh.

2. The electrolytic water vapor hydrogen production battery according to claim 1, characterized in that, The operating temperature of the electrolytic water vapor hydrogen production cell is the medium temperature; Preferably, the medium temperature is 100-250 °C.

3. The electrolytic water vapor hydrogen production battery according to claim 1, characterized in that, The polymer I containing quaternary ammonium salt groups and the polymer II containing quaternary ammonium salt groups are independently selected from at least one of polymers containing trimethylammonium groups, polymers containing piperidine groups, and polymers containing imidazole groups.

4. The electrolytic water vapor hydrogen production battery according to claim 1, characterized in that, In the exchange membrane, the quaternization degree of the quaternary ammonium salt groups is 70-100%.

5. The electrolytic water vapor hydrogen production battery according to claim 1, characterized in that, In the cathode and anode catalyst layers, the dosage of the polymer II containing quaternary ammonium salt groups is 20-80 wt%.

6. The electrolytic water vapor hydrogen production battery according to claim 1, characterized in that, In the cathode and anode catalyst layers, the dosage of the polymer II containing quaternary ammonium salt groups is 30-50 wt%.

7. The electrolytic water vapor hydrogen production battery according to claim 1, characterized in that, The water vapor enters the electrolytic water vapor hydrogen production cell from the anode end through water.

8. The electrolytic water vapor hydrogen production battery according to claim 7, characterized in that, The injection rate of the water is 0.02 to 1.0 mL / cm 2 min.